An Analysis of Maxim Violation In Sofia Vergara's Interview on The Ellen Show - Mardhatillah, Allifatul; Merrita, Diah (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2024)
This study aims to identify and analyze conversations that violate the principles of maxims in communication and to elucidate the violations of maxims by interpreting the contextual factors associated with these violations. The analysis is conducted using Grice’s theory of flouting maxim and Sperber and Wilson’s relevance theory on conversations in The Ellen Show program. A qualitative approach is used in this study to analyze and identify violations of communication principles that occur during these interviews. Out of twenty-seven cases, there are twenty cases where Grice’s maxims are violated. The maxim of quality has the highest frequency of violations, with eleven cases, or 55.0% of total violations. This is followed by maxims of manner and relevance, each with 14 (20.0%) and 13 (15.0%) cases respectively. The maxim of quantity has two cases of violation, accounting for 10.0% of the total. The dialogues between Ellen DeGeneres and Sofía Vergara show a significant presence of assumptions that are closely related to the specific context of their discussions and produce contextual effects that drive the conversation. The relevance of these assumptions is determined based on their ability to establish connections with the surrounding context and generate contextual effects, such as implications, contradictions, or strengthening. In general, their conversations illustrate the importance of contextual effects in establishing the significance of assumptions and influencing the course of a dialogue. Keywords: Maxim Violation, Relevance Theory, Contextual Effect